Property manager's knowledge and skills : a brief literature review towards achieving excellence / Mohd Zaki Arif and Rohaya Ghani - Arif, Mohd Zaki; Ghani, Rohaya (Unit for Research and Intellect Application (UfoRIA), 2009)
The development in landed properties haS increased the demand for Property Managers. The introduction of newer and modern building technology has changed the roles and functions of property managers. In order to develop and ensure good property management practices, property management in different countries is subjected to local rules and regulations. In Malaysia, property managers are required to register with The Board of Valuers, Appraisers and Estate Agents. However, complaints take place in the mass media, mainly on major areas such as technical knowledge, skills, attitude and abilities of the property managers. This triggers the need to identify and develop competency framework for property managers which is persistently referred as Knowledge, Skills, Abilities and Others (KSAOs). This paper outlines the critical knowledge, skills, abilities and other areas which are required by the property managers based on current literature. Views from related professions involving property management are also taken into consideration in identifying the KSAOs for the property managers. We are optimistic this paper will add to new knowledge on the topic of competency and property management. It is hopeful that property managers will boast a concerted effort in developing good property management practices by means of a competency-based management programme.